Immune microenvironment characteristics in multiple myeloma progression from transcriptome profiling - Wang, Jin; Hu, Yi; Hamidi, Habib; Dos Santos, Cedric; Zhang, Jingyu; Punnoose, Elizabeth; Li, Wenjin (Frontiers in Oncology, 2022)
Multiple myeloma (MM) is characterized by clonal expansion of malignant plasma cells in the bone marrow (BM). Despite the significant advances in treatment, relapsed and refractory MM has not yet been completely cured due to the immune dysfunction in the tumor microenvironment (TME). In this study, we analyzed the transcriptome data from newly diagnosed (ND) and relapsed/refractory (RR) MM patients in order to characterize differences in the TME and further decipher the mechanism of tumor progression in MM. We observed highly expressed cancer testis antigens and immune suppressive cell infiltration, such as Th2 and M2 cells, are associated with MM progression. Furthermore, the TFG-β signature contributes to the worse outcome of R/R MM patients. Besides, newly diagnosed MM patients could be classified into immune-low and immune-high phenotypes. Immune-high patients with higher IFN-g signatures are associated with MHC-II mediated CD4+T cell response through CIITA stimulation, which potentially influence the treatment efficacy of newly diagnosed MM in the case when ineligible for autologous stem cell transplantation (ASCT). Our study demonstrates how integrating tumor transcriptome and clinical information to characterize MM immune microenvironment and elucidate potential mechanisms of tumor progression and immune evasion, which will provide insights into MM treatments selection.